Sea slugs - divers' favorites, taxonomists' problems - Jensen, Kathe R (Universitas Sam Ratulangi, 2013)
Sea slugs, or opisthobranch molluscs, are small, colorful, slow-moving, non-aggressive marine animals. This makes them highly photogenic and therefore favorites among divers. The highest diversity is found in tropical waters of the Indo-West Pacific region. Many illustrated guidebooks have been published, but a large proportion of species remain unidentified and possibly new to science. Lack of funding as well as expertise is characteristic for taxonomic research. Most taxonomists work in western countries whereas most biodiversity occurs in developing countries. Cladistic analysis and molecular studies have caused fundamental changes in opisthobranch classification as well as â€œinstabilityâ€ of scientific names. Collaboration between local and foreign scientists, amateurs and professionals, divers and academics can help discovering new species, but the success may be hampered by lack of funding as well as rigid regulations on collecting and exporting specimens for taxonomic research. Solutions to overcome these obstacles are presented.Â Siput laut, atau moluska golongan opistobrancia, adalah hewan laut berukuran kecil, berwarna, bergerak lambat, dan tidak bersifat agresif. Alasan inilah yang membuat hewan ini sangat fotogenik dan menjadi favorit bagi para penyelam. Keanekaragaman tertinggi hewan ini ditemukan di perairan tropis Indo-Pasifik bagian Barat. Banyak buku petunjuk tentang hewan ini telah diterbitkan, tetapi sebagian besar spesimen belum teridentifikasi dan bisa menjadi hal baru bagi ilmu pengetahuan. Kekurangan dana dan keahlian merupakan cirikhas dari penelitian taksonomi. Umumnya para taksonom bekerja di negara-negara Barat sedangkan keanekaragaman tertinggi hewan ini berada di negara-negara berkembang. Analisis cladistik dan kajian molekuler menyebabkan perubahan mendasar dalam klasifikasi opistobrancia, demikian juga sering berubahnya nama ilmiah hewan ini. Kerjasama antara ilmuan lokal dan asing, amatir dan profesional, penyelam dan akademisi dapat membantu dalam menemukan jenis-jenis baru, tetapi keberhasilannya dapat dihambat oleh kurangnya biaya dan peraturan yang kaku dalam mengumpul dan mengirim spesimen untuk penelitian taksonomi. Solusi dalam menyelesaikan masalah tersebut disampaikan dalam tulisan ini.